Clinical status of hospitalized keloid cases from 2013 to 2018. Issue 8 (December 2022) - Zhu, Zhe; Kong, Weishi; Wang, Haibo; Xiao, Yongqiang; Shi, Ying; Gan, Lanxia; Sun, Yu; Tang, Hongtai; Xia, Zhaofan
Highlights: Prevalence of scars declined gradually in tertiary hospital admitted cases. Proportion of keloid increased yearly in hospitalized scar cases. Keloid cases had lower incidences of accompanied symptoms and higher surgical rate. Length of stay and cost were less in keloid cases than in non-keloid scar cases. Demographic and clinical features predict diagnosis of keloid at admission. Abstract: Objects: Keloids are intractable scar diseases and sometimes undergo hospitalization. This study aims to represent current status of keloid management in a national sample of hospitalized scar cases. Methods: Data of scar-diagnosed cases admitted in 1064 China's tertiary hospitals between 2013 and 2018, were obtained from the Hospital Quality Monitoring System (HQMS) database. Variables analyzed include sex, age, nationality, occupation, hospital department, accompanied symptoms at admission, surgical treatment, length of stay (LOS), and hospitalization cost. The potential risk factors of keloid diagnosis among scar cases were preliminarily identified through the Cochran-Mantel-Haenszel tests and univariate regression analyses. Results: This study identified 177, 586 scar cases including 21, 777 keloid cases and 155, 809 non-keloid scar cases. The prevalence of scars in the HQMS database was gradually decreased from 0.123% in 2013 to 0.075% in 2018. We found a preponderances of males (54.32%), adults (61.52%), Han nationality (93.38%), and students (17.35%) in scar cases, among whom keloid cases accounted for growing proportions increasing from 9.2% in 2013 to 15.1% in 2018. Comparing non-keloid scar cases, keloid cases consisted of more women (59.1% VS 43.8%), office staffs (13.08% VS 6.75%) and retirees (5.16% VS 2.65%), and less Zhuang (0.79% VS 1.40%) and Hui nationalities (0.76% VS 1.00%), and showed lower incidence of accompanied symptoms (4.51% VS 47.96%) and higher rate of receiving operations (57.96% VS 50.28%, P < 0.001). Both the LOS and cost per hospitalization were lower in keloid cases. Furthermore, the adult and older women, Han and Uyghur nationalities, office staffs and retirees, and admitted in otolaryngology and dermatology departments, were potential predictors of keloid diagnosis among hospitalized scar cases. Conclusion: When viewed at the national level, keloid occupies an important part in scar management in Chinese tertiary hospitals. Demographic and clinical differences between keloids and other scars facilitate understanding and promoting of individualized anti-scar therapeutic strategies.